2015
DOI: 10.1002/pmj.21469
|View full text |Cite
|
Sign up to set email alerts
|

An Inquiry to Move an Underutilized Best Practice Forward: Barriers to Partnering in the Architecture, Engineering, and Construction Industry

Abstract: There is an obvious need in the architecture, engineering, and construction (AEC) industry for improved project team integration through project delivery to ensure improved project outcomes. The literature reports that, among other methods, project partnering, when followed successfully, provides a great opportunity to improve project performance via improved collaboration among key project stakeholders (e.g., owner, designer, contractor) and reduce claims as a result while letting all project members stay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…On a more strategic level, Crespin-Mazet and Portier (2010) suggest that the lack of diffusion and understanding of construction partnering may be due to the resistance of purchasers who feel threatened by the structural changes in their purchasing habits. According to Mollaoglu et al (2015), of the top reported barriers to project partnering, the majority are cultural; and contrary to the literature according to them, none are legislative. On the other hand, factors such as "Faster construction time", "Improvement of relationship amongst project participants" and "Improvement in communication amongst project participants" have been stated as significant benefits (Chan et al, 2003a).…”
Section: Partneringmentioning
confidence: 89%
“…On a more strategic level, Crespin-Mazet and Portier (2010) suggest that the lack of diffusion and understanding of construction partnering may be due to the resistance of purchasers who feel threatened by the structural changes in their purchasing habits. According to Mollaoglu et al (2015), of the top reported barriers to project partnering, the majority are cultural; and contrary to the literature according to them, none are legislative. On the other hand, factors such as "Faster construction time", "Improvement of relationship amongst project participants" and "Improvement in communication amongst project participants" have been stated as significant benefits (Chan et al, 2003a).…”
Section: Partneringmentioning
confidence: 89%
“…Factors specific to project partnering include early involvement of contractors and dialogues to manage conflicts with the purpose of building trust (Mollaoglu et al, 2015, Eriksson, 2010, Lahdenperä, 2012, and joint objectives and joint risk mitigation between client and contractor in pursuit of improved performance (Walker and Lloyd-Walker, 2015). In this paper, we use the definition by Børve et al (2017): "Project Partnering is a relationship strategy whereby a project owner integrates contractors and other major contributors into the project.…”
Section: Partnering Success Factorsmentioning
confidence: 99%
“…Similarly, in a recent study of barriers to partnering, Mollaoglu et al (2015) found that cultural barriers were the common obstacles listed by respondents. These attitudinal barriers included lack of trust, misunderstanding of partnering among the members, and communication problems.…”
Section: Theoretical Foundation Collaboration In Construction Projectsmentioning
confidence: 88%
“…Partnering represents a fundamental shift away from the traditional adversarial and short-term relationships in construction (Barlow & Jashapara, 1998; Bresnen & Marshall, 2000; Bygballe, Jahre, & Swärd, 2010; Crespin-Mazet, Havenvid, & Linné, 2016; Gadde & Dubois, 2010; Wood & Ellis, 2005). However, despite the perceived benefits of partnering and the identification of a range of critical success factors (Black, Akintoye, & Fitzgerald, 2000; Chan et al, 2004), partnering remains an elusive concept (Bresnen & Marshall, 2000) and its impact on performance ambiguous (Beach, Webster, & Campbell, 2005; Bresnen, 2010; Bresnen & Marshall, 2010; Hartmann & Bresnen, 2011; Jacobsson & Roth, 2014; Mollaoglu, Sparkling, & Thomas, 2015; Nystrom, 2005). By examining the role of routines in partnering, we aim to contribute to the understanding of partnering and what might explain how and why it is likely to succeed.…”
Section: Introductionmentioning
confidence: 99%